Relativism, realism, and reflection - Tasioulas, J (Routledge, 1998)
This paper undertakes a critical examination of three key strands - relativism, anti-realism, and reflection - in Bernard Williams's sceptical interpretation of ethical thought. The anti-realist basis of Williams's 'relativism of distance' is identified and the way this threatens to render his relativism more subversive than initially appears. Focusing on Williams's anti-realism, the paper argues that it fails because it is caught on the horns of a dilemma: either it draws on a conception of reality that is metaphysically incoherent, or else it employs a 'best explanation' criterion that question-beggingly excludes from further consideration the sort of reason-based explanations that disclose ethical properties to be real. Finally, it is noted that Williams's relativism and anti-realism destabilize his picture of ethical reflection.